Pengaruh Tingkat Pengembalian Ekuitas, Rasio Utang atas Ekuitas dan Rasio Lancar Terhadap Perubahan Laba : Penelitian - Dhuhaika Alisnaeni Walagustiani; Zain Zainuddin; Nita Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The aim of this research is to assess the influence of Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) on profit fluctuations. This study utilizes a quantitative approach with purposive sampling, focusing on 8 companies within the transportation and logistics sector that are listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Data analysis is performed using multiple linear regression techniques with panel data, analyzed through E-Views 12 software. The findings reveal that Return on Equity has a positive and significant impact on profit changes when considered individually. Conversely, both the Debt to Equity Ratio and Current Ratio exhibit a negative and significant effect on profit changes. Collectively, these three variables are shown to significantly influence the company's profit changes. The distinctiveness of this research is found in its thorough examination of the transportation sector during the COVID-19 pandemic, offering new perspectives on the industry's financial resilience.